Coherence lifetime broadened optical transitions in a 2 atom diameter HgTe nanowire: a temperature dependent resonance Raman study. Issue 98 (6th October 2016) - Spencer, Joseph H.; Smith, David C.; McDonnell, Liam P.; Sloan, Jeremy; Kashtiban, Reza J.
Abstract : The paper sets out the role of electronic coherence in the strong temperature dependence of the intensity of Raman scattering from two atom diameter HgTe nanowires. It argues the behavior is likely common in extreme nanowires, and possibly due to excitonic effects. Abstract : This paper presents the results of measurements of the temperature dependence of resonance Raman scattering from 2 atom diameter HgTe nanowires embedded in the central pore of single walled carbon nanotubes, over the temperature range 4–295 K and excitation photon energies in the range 1.65 to 1.90 eV. The spectra are analysed to extract the temperature dependence of the phonon energies and linewidths and the central energy, linewidth and peak scattering strength of the optical resonances. The temperature dependence of the peak scattering strength is explained by a model in which the resonance broadening is dominated by coherence lifetime broadening, allowing us to determine the coherence lifetime of the underlying optical transition: 9 fs at 295 K and 18 fs at 50 K. The results are comparable with similar results on carbon nanotubes which suggests that the optical transitions responsible for the Raman resonances are excitonic.